COVID-19 mortality and the overweight: Cross-Country Evidence - Bernard Arulanandam; Hamid Beladi; Avik Chakrabarti (Elsevier, 2021)
Objective(s): The objective is to study the role, if any, of excess body weight in COVID-19 mortality. Study design: This is a cross-country study of plausible associations between COVID-19 mortality and the proportion of overweight among adults, controlling for age, gender, and income. Methods: Parametric and non-parametric regression analysis. Results: We observe a statistically significant positive association between COVID-19 mortality and the proportion of the overweight in adult populations spanning 154 countries. This association holds across countries belonging to different income groups and is not sensitive to a population's median age, proportion of the elderly, and/or proportion of females. The estimated elasticities of COVID-19 mortality, with respect to the proportion of the overweight in adult populations, are consistently higher for sub-samples of countries that belong to a higher income group. On an average, every percentage point increment in the proportion of the overweight in adult populations contributes to an additional 3.5% points to COVID-19 mortality for high income countries: the limits of confidence intervals around this point estimate range between 1.5 and 5.4. Conclusions: A positive association between COVID-19 mortality and the proportion of the overweight in a country's adult population is robust, subject to alterations in the conditioning information set on age, gender, and income. Our findings call for an effective alignment of public policy regulations with public health priorities.